Réponses

Meilleure réponse !
  • Utilisateur Brainly
2014-05-04T15:03:18+02:00
(6 x – 2)²- (x+4)² =0


((6 x – 2)- (x+4)][(6 x – 2)+ (x+4)] =0

(6x-2-x-4)(6x-2+x+4) = 0

(5x-6)(7x+2) = 0

5x-6 = 0
5x = 6
x = 6/5

7x+2 = 0
7x = -2
x =-2/7



2014-05-04T15:05:56+02:00
Salut :) :)


(6 x – 2)²- (x+4)² =0

Alors
(6 x – 2)
(6 x – 2) - (x+4)(x+4) =0

(5x-6) (7x+2) = 0

35x²-32x-12 = 0

Soulution

x = - \frac{2}{7}







oui .
merci quand même :)
hhhhhhh mais la meme soulution hhhhhh
Oui c vrai mais pas la deuxième: 6/5
je ris